Simulation of orthogonal frequency division multiplexing (OFDM) signaling - Mastura Ibrahim
The aim of this final year project is to investigate OFDM communication systems, as well as to study the OFDM signaling through MATLAB simulation for communication systems. Besides that, this project is done in order to demonstrate some of the basic concept and the strength of OFDM in multipath channel.